Air Bag Momentum Force Including Aspiration - Guy Nusholtz; Deguan Wang; E. Benjamin Wylie (Shock and Vibration)
A gas-jet momentum force drives the air bag into position during a crash. The magnitude of this force can change as a result of aspiration. To determine the potential magnitude of the effect on the momentum force and mass flow rate in an aspirated system, a series of experiments and simulations of those experiments was conducted. The simulation consists of a two-dimensional unsteady isentropic CFD model with special “infinite boundaries”. One of the difficulties in simulating the gas-jet behavior is determining the mass flow rate. To improve the reliability of the mass flow rate input to the simulation, a sampling procedure involving multiple tests was used, and an average of the tests was adopted.